Podejście eklektyczne w nauczaniu polszczyzny za granicą na przykładzie wiersza Stanisława Barańczaka Garden party - Lipińska, Ewa (Postscriptum Polonistyczne, 2020)
The article discusses the problem of teaching Polish as a heritage language, outside of Poland and when the number of teaching hours is limited. In such a situation it is worthwhile to integrate subsystems and language skills as well as combining the curricula of a range of subjects. This eclectic approach seems to be effective here. The approach is described not as a set of random actions, but as wellthought out and coherent procedures. The article uses the example of Barańczak’s Garden party to present how different techniques can be applied in teaching. It also underlines the necessity of using different media, which makes language education more modern and more attractive.